Endogenous Presidentialism. Issue 4 (27th June 2016) - Robinson, James A.; Torvik, Ragnar
Abstract: We develop a model to understand the incidence of presidential and parliamentary institutions. Our analysis is predicated on two ideas: first, that minorities are relatively powerful in a parliamentary system compared to a presidential system, and second, that presidents have more power with respect to their own coalition than prime ministers do. These assumptions imply that while presidentialism has separation of powers, it does not necessarily have more checks and balances than parliamentarism. We show that political leaders who prefer presidentialism may be supported by their own coalition if they fear losing agenda-setting power to another group. We argue that the model is consistent with a great deal of qualitative information about presidentialism in Africa and Latin America.